PV System Multiple Source Single Inverter (International Journal of Innovative Research in Computer Science & Technology, 2022)
Renewable energy has gotten a lot of  attention because of environmental issues like climate  change, as well as political and economic reasons  including decreased reliance on foreign energy imports and  high oil costs. The fastest-growing renewable energy  industries are wind and solar power. As advances in  renewable energy are developed, the cost of power  generated by renewable energy decreases. Renewable  energy technologies are excellent for dispersed power  generation as well as solving climate change and reducing  reliance on foreign energy imports. Renewable energy may  deliver power without expensive and intricate grid  infrastructure in distant, there are really no power sources  in remote areas, or the expense of installing distribution  networks is prohibitive. Power capacity built worldwide reached 227 gigawatts  (GW) in 2015, enough to need 1% of total electricity  generation. Thermal power plants may be located in  northern Argentina, with the largest being the 392 MW  Ivanpah Solar Electric Generation System in Arizona. This paper describes and analyses a micro-grid system that  includes different and independent PV sources connected  to a shared DC bus, as well as localized battery storage and  power monitoring and protection devices.
Keywords: Solar Energy; Thermal Energy; Power Protection; Microgrid